TINGKAT LITERASI KEUANGAN SYARIAH PELAKU UMKM DAN PENGARUHNYA TERHADAP PERKEMBANGAN UMKM DI KECAMATAN JEPARA - Surepno Surepno; Siti Halimatus Sa’diyah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to determine the level of financial literacy of MSME actors in Jepara District and analyze the influence of financial knowledge, financial behavior, financial attitude on the development of MSMEs on MSME actors in the trade sector and processing industry (food products, beverages, and services) in Jepara District. This study uses a quantitative approach using the questionnaire method in data collection. The population in this study were MSME actors engaged in the trade and processing industries (food products, beverages, and services) in Jepara District as many as 242 businesses. The samples studied were 75 respondents who were calculated using the Slovin formula. The data analysis technique used is multiple linear regression analysis. The research results obtained are financial knowledge, financial behavior and financial attitude have a positive effect on the development of MSMEs.